Occurrence of parasitic zoonosis in the traditions «Los ratones de fray Martín» and «El primer toro» - Nima Polo, Nicole Alexandra (2023)
This article will analyse the occurrence of parasitic zoonosis in the traditions «Los ratones de fray Martín» and «El primer toro», in which Ricardo Palma shows us the rejection of people towards «unpleasant» animals, due to the belief that they were carriers of diseases that affected humans. Likewise, the aim of this work is to highlight the role of the veterinary doctor in the prevention and treatment of diseases transmitted between animals and humans.